Description of Process Skills of Students with Dyscalculia in Understanding the Concept of Counting Operations Through Ethnomathematics - Ajeng Retno Pramesti; Kamid Kamid; Rohati Rohati (MASI Mandiri Edukasi, 2025)
Mathematics is fundamental in daily life and education, yet students with dyscalculia face significant challenges in mastering basic arithmetic operations. This study investigates how the ethnomathematics approach can develop process skills among students with dyscalculia. Using a qualitative descriptive method, two grade-six students with different levels of dyscalculia were studied through observations, tests, and interviews. Results indicate that students with moderate dyscalculia (S1) demonstrated progress in classification and calculation with minimal guidance, while those with severe dyscalculia (S2) required intensive support and showed limited progress. This suggests that ethnomathematics, which integrates cultural and contextual learning, is effective for students with learning disabilities but requires adaptation based on severity levels. Findings highlight the potential of culturally relevant methods in enhancing mathematical skills.